EFFECTS OF SOAKING FEET WITH WARM WATER SOLUTION OF LEMONGERAH (CYMBOPOGON CITRATUS ) ON BLOOD PRESSURE IN HYPERTENSION PATI - budiono budiono; Wadzifatu Qurrotu Aini; Abd. Hanan; Edy Suyanto (Jurnal Keperawatan Terapan, 2024)
Hypertension is one of the main risk factors that contributes significantly to the incidence of heart disease. Chronic high blood pressure conditions cause the heart's workload to increase, which can cause left ventricular hypertrophy and ultimately lead to heart failure and cause sudden death in sufferers. PThis research aims to determine the effect of soaking feet in warm water with a solution of lemongrass (cymbopogon citratus ) on blood pressure in hypertensive patients This research design uses Pre Experimental Design with the type of plan One Group Pretest Posttest. The sample used was 34 respondents in accordance with the predetermined inclusion and exclusion criteria, using a sampling probability. Researchers measured blood pressure in respondents before and after soaking their feet in warm water with a solution of lemongrass (Cymbopogon Citratus), then blood pressure was observed again after therapy, then analysis was carried out using the paired sample t-test ? (0,05). The results of the research based on the results of the paired t-test showed a p value of 0.00 < 0.05, the effect of foot baths using warm water with a solution of lemongrass (cymbopogon citratus) on the decrease in blood pressure showed that there was a significant difference between the blood pressure of hypertensive patients before and after being given warm water with a p value = 0.00, there was a decrease in the average systolic blood pressure of 10.31 mmHg. Soak your feet in warm water with a lemongrass solution (cymbopogon citratus) can reduce blood pressure in hypertensive patients. Thus, foot soak therapy uses warm water with a solution of lemongrass (cymbopogon citratus), can be used as an alternative intervention to reduce blood pressure in patients suffering from hypertension